Revitalisasi Gotong Royong Untuk Pengelolaan Sampah Di Kelurahan Sawah Lebar Kota Bengkulu - Maria Agustina Br.Nambela; Aditya Dwi Kurniawan; Ofta Prastiyo Apriansyah; Panji Dwi Atmojo; Muhammad Bendy; Prahasti Prahasti; Leni Natalia Zulita; Karona Cahya Susena (Utami Publisher, 2026)
Gotong royong is a noble tradition of the Indonesian people that has declined in the modern era, particularly in urban areas. This study examines the revitalisation of the gotong royong culture as a strategy for sustainable waste management in RT 08 RW 02, Sawah Lebar Village, Bengkulu City. The main issues include low resident participation in collective activities, a lack of awareness regarding waste sorting, and a shortage of environmental education materials. Implementation methods included Focus Group Discussions, scheduled community work sessions, the installation of visual educational materials, waste sorting training, and a partnership with the Waste Bank. The results of the activities showed an increase in resident participation to 75%, the installation of educational signs on waste decomposition periods, the implementation of a mandatory reporting system for boarding house residents, and the successful deposit of plastic waste at the Waste Bank. This programme successfully fostered collective community awareness in maintaining environmental cleanliness by utilising the local wisdom of community cooperation.